Parent’s Satisfaction Level with Child Health Services in Puskesmas in BPJS Era - Ansori, Moch. Afrizal; Irwanto, Irwanto; Handayani, Samsriyaningsih (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2022)
In BPJS era, health facilities are demanded to be able to adjust their health care policies according to BPJS standards with a number of limitations. This study aimed to measure the level of parental satisfaction with child health services in Puskesmas in BPJS era. This type of research was observational descriptive using a service quality (servqual) questionnaire. The sample size in this study was 100 respondents. From 100 participants, it was found that 11% were very satisfied, 15% were satisfied and 74% were dissatisfied with children's health service in puskesmas. The overall satisfaction result calculated from the gap between the perception and the expectations of the respondents towards children's services in puskesmas is -0.4635, which means that the service is still unsatisfactory. The results of Importance Performance Analysis (IPA) show that the priority scale of improvement of children's health services in puskesmas from high to low priority are Tangibles and Reliability, Responsiveness, Assurance, and Empathy. This study shows that the level of parental satisfaction with children's health services in puskesmas is still low or unsatisfactory. Puskesmas should focus on improving the quality of BPJS child health services on items that are in the top priority quadrant.